Nickel(0)‐Mediated Transformation of Tetrafluoroethylene and Vinylarenes into Fluorinated Cyclobutyl Compounds. Issue 9 (23rd January 2017) - Ohashi, Masato; Ueda, Yuta; Ogoshi, Sensuke
Abstract: In the presence of Ni 0 /PCy3, styrene was found to participate in oxidative cyclization with tetrafluoroethylene, thus leading to the corresponding nickelacycle with a unique η 3 ‐π‐benzyl structure. In addition, the flexibility of the coordination mode in the η 3 ‐benzyl moiety allowed the partially fluorinated nickelacycle to undergo unprecedented amine‐induced α‐fluorine elimination, thus leading to the construction of a fluorinated cyclobutyl skeleton. Abstract : In the presence of Ni 0 /PCy3, styrene was found to participate in oxidative cyclization with tetrafluoroethylene, thus leading to the corresponding nickelacycle with a unique η 3 ‐π‐benzyl structure. In addition, the flexibility of the coordination mode in the η 3 ‐benzyl moiety allowed the partially fluorinated nickelacycle to undergo unprecedented amine‐induced α‐fluorine elimination, thus leading to the construction of a fluorinated cyclobutyl skeleton.